A Short Survey on Surfaces Endowed with a Canonical Principal Direction - Kelleci, Alev; Ergut, Mahmut (Istanbul Technical Univ, 2017)
In this paper, we would like to give a short survey of recent results on hypersurfaces with canonical principal direction relative to a fixed direction in a (semi-)Riemannian manifold. We also present some of our first results that we have recently obtained in this direction.
International Workshop on Theory of Submanifolds -- JUN 02-04, 2016 -- Istanbul Tech Univ, Istanbul, TURKEY
Keywords: Minkowski space; Lorentzian surfaces; canonical principal direction; Generalized constant ratio submanifolds